Penambahan Tepung Cangkang Kerang Simping (Placuna Placenta) Terhadap Peningkatan Kalsium, Fosfor dan Magnesium Pada Pakan - Karim, Mutemainna; Ardiansyah, Ardiansyah; Sofyan, Jawiana Saokani; Nursyahran, Nursyahran (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi dan Bisnis Maritim Balik Diwa, 2025)
This study aimed to evaluate the potential of scallop shell meal (Placuna placenta) as a natural mineral source to increase calcium (Ca), phosphorus (P), and magnesium (Mg) content in fish feed formulations. The study used an experimental design with four treatments of shell meal supplementation levels (0%, 10%, 20%, and 30%). Laboratory analysis showed that increasing the concentration of scallop shell meal significantly increased the levels of Ca and Mg in the feed, with the highest values being 92,656.67 µg/g and 2,006.03 µg/g, respectively, at the 30% treatment. Conversely, phosphorus levels decreased with increasing shell meal dosage. The results of the ANOVA test and Tukey's follow-up test showed significant differences (p<0.05) between treatments. This study proves that scallop shell meal can be used as an effective, inexpensive, and environmentally friendly natural mineral additive in fish feed, especially in supporting bone mineralization and energy metabolism